Counter-terrorism after 9-11 justice, security, and ethics reconsidered - Crank, John P.; Gregor, Patricia E. (LexisNexis, 2005)
This book provides the reader with a sense of the breadth of government activity, its nature, and the surrounding controversies, by looking at the many different facets of the war on terrorism. Terrorism and counter-terrorism are defined, and the following topics are discussed, in the context of counter-terrorism, post-9/11: surveillance; preparation for terror; detainment and seizure, and registration and surveillance, of Middle-Eastern immigrants in the United States since 9/11; Guantanamo Bay and the treatment of foreign prisoners; critical and ethical assessments of the War on Terror; and considerations of governing a free society.